Female infidelity is constrained by El Niño conditions in a long‐lived bird. (31st May 2016) - Kiere, Lynna Marie; Drummond, Hugh
Summary: Explaining the remarkable variation in socially monogamous females' extrapair (EP) behaviour revealed by decades of molecular paternity testing remains an important challenge. One hypothesis proposes that restrictive environmental conditions (e.g. extreme weather, food scarcity) limit females' resources and increase EP behaviour costs, forcing females to reduce EP reproductive behaviours. For the first time, we tested this hypothesis by directly quantifying within‐pair and EP behaviours rather than inferring behaviour from paternity. We evaluated whether warmer sea surface temperatures depress total pre‐laying reproductive behaviours, and particularly EP behaviours, in socially paired female blue‐footed boobies ( Sula nebouxii ). Warm waters in the Eastern Pacific are associated with El Niño Southern Oscillation and lead to decreased food availability and reproductive success in this and other marine predators. With warmer waters, females decreased their neighbourhood attendance, total copulation frequency and laying probability, suggesting that they contend with restricted resources by prioritizing self‐maintenance and committing less to reproduction, sometimes abandoning the attempt altogether. Females were also less likely to participate in EP courtship and copulations, but when they did, rates of these behaviours were unaffected by water temperature. Females' neighbourhood attendance, total copulation frequency and EP courtship probability responded to temperature differences at the between‐season scale, and neighbourhood attendance and EP copulation probability were affected by within‐season fluctuations. Path analysis indicated that decreased EP participation was not attributable to reduced female time available for EP activities. Together, our results suggest that immediate time and energy constraints were not the main factors limiting females' infidelity. Our study shows that El Niño conditions depress female boobies' EP participation and total reproductive activity. In addition to increasing general self‐maintenance and reproductive costs, warm waters may increase costs specific to EP behaviours including divorce, reduced male parental care, or pathogen exposure. Our results suggest that female boobies strategically refrained from EP behaviours to avoid these or other longer‐term costs, rather than being compelled by immediate constraints. This study demonstrates that current environmental conditions affect females' mating decisions, contributing to variation in EP behaviours, even in a long‐lived, iteroparous species that can buffer against temporary adversity. Abstract : Famous for sparking floods and for devastating the survival and reproduction of marine predators, El Niño has now been tagged with putting a bird off sex. Despite having the wherewithal to survive the most extenuating events, female blue‐footed boobies tone down their mating activities, cutting back even on their infidelity.